2020
DOI: 10.1182/blood.2020006000
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and its implications for thrombosis and anticoagulation

Abstract: Severe acute respiratory syndrome coronavirus 2, coronavirus disease 2019 (COVID-19)-induced infection can be associated with a coagulopathy, findings consistent with infection-induced inflammatory changes as observed in patients with disseminated intravascular coagulopathy (DIC). The lack of prior immunity to COVID-19 has resulted in large numbers of infected patients across the globe and uncertainty regarding management of the complications that arise in the course of this viral illness. The lungs are the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

63
2,391
3
140

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 2,165 publications
(2,714 citation statements)
references
References 68 publications
63
2,391
3
140
Order By: Relevance
“…These ndings indicated that excessive activation of the coagulation cascade and PLTs existed in the progression of COVID-19 infection. The underlying mechanisms of activated coagulation remain unclear but may be due to in ammatory responses induced by SARS-CoV-2 [61]. Coagulation screening, especially the determination of D-dimer and PLT levels, has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings indicated that excessive activation of the coagulation cascade and PLTs existed in the progression of COVID-19 infection. The underlying mechanisms of activated coagulation remain unclear but may be due to in ammatory responses induced by SARS-CoV-2 [61]. Coagulation screening, especially the determination of D-dimer and PLT levels, has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The disease has been revealed as a systemic disease, the increased expression of ACE2 in patients with comorbidities may represent a propensity for an increased viral load of infection and the spread of the virus to extrapulmonary tissues (4,5). This systemic virus dissemination brings complications to different organs of the body in patients who evolve for the severe clinical form, which may affect central nervous system, eyes, heart and gut, leading to multi-organ dysfunction and extensive microthrombus formation with multiorgan failure (6). Evidences have shown that patients recovering from COVID-19 infection show signs of antiviral T and B cellmediated adaptive immunity and memory, with clonal expansion and activation (7).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of pulmonary embolism in the ICU is near 20% (40). ISTH and the American Society of Hematology recommended prophylactic dose of low molecular weight heparin to prevent thrombotic event (47)(48)(49). Even with thromboprophylaxis, 7.7% of patients in academic hospital of Milan developed thrombotic event (50).…”
Section: Discussionmentioning
confidence: 99%